Performance of Sieve net Bycatch Reduction Devices in the Seas off Cochin (Southwest Coast), India - S., Sabu; T.R., Gibinkumar; P., Pravin; M.R., Boopendranath (Fishery Technology, 2025)
Bottom trawling is widely employed for catching shrimps in India. Due to the multi species nature of Indian fisheries, bottom trawling catches considerable amount of non-shrimp resources, especially juveniles. Performance of two designs of Sieve net Bycatch Reduction Devices was evaluated in the seas off Cochin, southwest coast of India. Designs selected were Sieve net (i) with a 60 mm diamond mesh funnel inside the net and 80 mm diamond mesh outlet codend (Sieve net-60) and (ii) with 50 mm diamond mesh funnel inside the net with 60 mm diamond mesh outlet codend (Sieve net-50). Among the two Sieve nets evaluated, Sieve net-60 performed better in terms of shrimp retention. Bycatch exclusion in Sieve net-60 was about 37% (without jellyfish) and 15% (with jellyfish) while bycatch exclusion in Sieve net-50 operated during non-jelly fish season was 33%. Shrimp loss was 4.5% and 19.5% in Sieve net-60 and Sieve net-50, respectively. Marketable size groups of fishes and crabs were retained in outlet codends of the Sieve net BRDs. Sieve nets can also be efficiently used to exclude jellyfish when they are abound in the shrimp fishing grounds, by keeping the outlet codend open. Sieve net-60 has potential for adoption in tropical trawl fisheries, in order to minimize the impact of shrimp trawling on juveniles and non-targeted species.